Меню

УСЛОВИЕ:
решить 7 класс... (0,001)^5*10^10/10^4
27^-2 * 9^2/3^-4
0,25^3*16^2/2^4
(корень 8 -4 корня из 3 + корень из 12)* корень из 2
(1-корень из 5)^2
корень 12 +3 корня из 6 /3 корня из 6
( корень 7 -1 )^2
корень 6 -3 корня из 2/3 корня из 2
где /- знаменатель! ^ -степень



РЕШЕНИЕ:$$ \frac{(0,001)^5 *10^{10}}{10^4} = (10^{-3})^5 *10^{10}*10^{-4} = 10^{-15+10+(-4)}=10^{-9} $$

$$ \frac{27^{-2} *9^2}{3^{-4} }= (3^{3})^{-2} * (3^2)^2 *3^4 = 3^{-6 +4 +4} = 3^2=9 $$

$$ \frac{0.25^3 *16^2}{2^4} =(\frac{1}{4}) ^3 *( 2^4)^2 * 2^{-4} = ( 2^{-2})^3 * 2^8 *2^{-4} = 2^{-2} = \frac{1}{4} $$

(√8 - 4√3+√12)*√2=  (2√2 -4√3 +2√3) *√2 = (2√2-2√3)*√2=
= 2√2 *√2  - 2√3*√2 = 2*2  -2√6 = 4-2√6

(1-√5)² = 1² -2*1*√5 + (√5)² = 1-2√5+5 =6-2√5

(√12 +3√6)/ 3√6 =  (2√3+3√6) /3√6  =
=3√6(2√3 +3√6) / (3√6 *3√6) =
= (18√2 + 54) / 54 =  18(√2+3) /  (18*3) =
 = (√2+3)/3  = √2/3  +1

(√6-3√2 ) / 3√2 =  3√2(√6 -3√2) /  (3√2  *3√2) =
= (6√3 -18)/18 = 6(√3-3)/ (6*3) = (√3-3)/3 = √3/3  -1

Вариант решения:

$$ 1)\; \; \frac{(0,001)^5\cdot 10^{10}}{10^4}= \frac{10^{-15}\cdot 10^{10}}{10^4} =10^{-15+10-4}=10^{-9}\\3)\; \; \frac{0,25^3\cdot 16^2}{2^4}= \frac{2^{-6}\cdot 2^8}{2^4} =2^{-6+8-4}=2^{-2}=0,25\\2)\; \; \frac{27^{-2}\cdot 9^2}{3^{-4}}= \frac{3^{-6}\cdot 3^4}{3^{-4}} =3^{-6+4+4}=3^2=9\\4)\; \; (\sqrt8-4\sqrt3+\sqrt{12})\cdot \sqrt2=(2\sqrt2-4\sqrt3+2\sqrt3)\cdot \sqrt2=\\=2\cdot 2-2\sqrt3\cdot \sqrt2=4-2\sqrt6=2\sqrt2(\sqrt2-\sqrt3)\\5)\; \; (1-\sqrt5)^2=1-2\sqrt5+5=6-2\sqrt5=2(3-\sqrt5) $$

$$ 6)\; \; \frac{\sqrt{12}+3\sqrt6}{3\sqrt6}= \frac{\sqrt6(\sqrt2+3)}{3\sqrt6} = \frac{\sqrt2+3}{3} =1+\frac{\sqrt2}{3}\\7)\; \; (\sqrt7-1)^2=7-2\sqrt7+1=8-2\sqrt7=2\cdot (4-\sqrt7)\\8)\; \; \frac{\sqrt6-3\sqrt2}{3\sqrt2}= \frac{\sqrt6(1-\sqrt3)}{3\sqrt2} =\sqrt3\cdot (1-\sqrt3) $$






Похожие примеры: